THE METHOD ESTIMATION PARAMETERS SIGNAL OF MEANS OF UNAUTHORIZED REMOV-AL OF INFORMATION ON THE BASIS OF CORRELATION-REGRESSION ANALYSIS - Лаптєв, Олександр Анатолійович; Войченко, Тетяна Олександрівна; Кудюкін, Павло Вікторович; Степаненко, Володимир Іванович (Science-based technologies, 2019)
The article deals with the development of a model based on an experimentally statistical approach. The real method of obtaining mathematical models is not experimental-analytical but experimental approaches. As the data can be used the results of the activities, expert assessments. That is, the main sources of raw data is a really accumulated static database of a particular type of process or method under study. Theoretical - mathematical approach in most cases of its realization simplifies reality, generalizing, ignoring features and individuality. The experimental-statistical approach builds its models on individual, specific data that does not detach the object from the time and place frames. A method of regression analysis that can be used to determine the parameters of bookmarks related to a specific parametric series - in order to probabilistically find the signals of radio bookmarks that differ from each other in terms of technical characteristics and principle of operation is considered. This method is used to analyze and justify the level and other properties of signals, characterized by the presence of one or more parameters, showing the basic properties of radio bookmarks. Regression analysis allows us to find an empirical formula that describes the dependence of detecting a radio bookmark signal on parameters that distinguish different types of radio bookmarks. Based on this method, a radio bookmark search model is constructed. As input parameters, the real results of the events were used, ie the main sources of output are the actual static base for checking the objects for radio bookmarks. The method of estimation of mutual influence of parameters of a radio bookmark signal on the basis of correlation - regression analysis of practical search results, for a multidimensional process is developed. On the basis of real statistics correlation-regression analysis of influence of search parameters of bookmarks was carried out. The adequacy of the data obtained was evaluated by two different methods. Fechner coefficient approval and Pearson coefficient determination. Both methods of assessment showed almost identical results, which is a confirmation of the model's adequacy and fully correspond to the practical aspect of finding radio bookmarks.